Dampak Kegiatan Remaja Masjid Terhadap Perilaku Keagamaan Remaja Di Jorong Taratak Baru Kenagarian Salimpat Kabupaten Solok - Nike Setria Andani; Wedra Aprison (Simpati, 2023)
This research was motivated by mosque youth in Jorong Taratak Baru, Salmpat district, Solok district, that teenagers whose behavior did not reflect themselves as mosque youth. For this reason, researchers tried to examine the Impact of Youth Mosque Activities on Teenagers' Religious Behavior. This type of research is field research (field research) using a quantitative approach that is correlational. Enlti conducted research at the Jorong Taratak Baru Tauhid Mosque, Kenagarian Salimpa, Solok Regency. In collecting data the researcher used a questionnaire. Meanwhile, to analyze it, the researcher conducted a prerequisite test, namely the normality test and correlation test using the product moment correlation formula. After the research was carried out, it could be concluded that there was a positive impact on youth mosque activities on the religious behavior of mosque youth in Jorong Taratak Baru Kenagarian Salimpat, Solok Regency. This can be seen from the results of Asymp. Sig. (2-tailed) of 0.00 <0.05. So it can be said that there is a relationship between the activities of youth in the mosque and the religious behavior of adolescents which has a positive impact on the religious behavior of adolescents.